Exploring the Hepatoprotective Effect of Agaricus bisporus Based on Network Pharmacology - WANG Jie, WANG Jinmei, LIU Hui, LIU Xuguang, GUO Wenjing, HE Hongping (Shipin Kexue)
To investigate the hepatoprotective components and mechanism of Agaricus bisporus ethanol extract (ABEE), ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to analyze and identify the components of ABEE. The active components and mechanism were analyzed using network pharmacology and a mouse model of CCl4-induced acute liver injury. UPLC-MS/MS analysis identified 75 compounds, of which 15 were predicted by network pharmacology to be related to liver injury, with 11 different targets. Animal experiments showed that ABEE significantly alleviated CCl4-induced acute liver injury in mice. Compared with the model group, the high-dose group (1 000 mg/kg) showed significant recovery in liver function indicators such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (AKP) (P < 0.001). The antioxidant capacity in mice was significantly enhanced, as evidenced by a significant increase in superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities (P < 0.001) and a significant decrease in malondialdehyde (MDA) content (P < 0.01). Detection of the mRNA and protein expression levels of relevant genes was performed using real-time quantitative polymerase chain reaction (PCR) and Western blot techniques, showing that compared with the model group, the expression of the Bcl-2 in the high-dose group significantly increased (P < 0.001), while the expression of MYC, NF-κB1, RELA and MMP9 significantly decreased (P < 0.01). These results confirmed the predictions, indicating that ABEE might exert its hepatoprotective effect by regulating the expression of Bcl-2, MYC, NF-κB1 and RELA through salicylic acid, palmitic acid, linolenic acid, and chrysin, as well as their associated signaling pathways such as chemical carcinogenesis-receptor activation. This study suggests that ABEE may provide liver protection by inhibiting apoptosis, carcinogenesis, and lipid peroxidation caused by free radicals through multiple components, targets, and pathways.